Discovery of a lunar air temperature tide over the ocean: a diagnostic of air-sea coupling. Issue 1 (December 2018) - Sakazaki, T.; Hamilton, K.
Abstract The lunar semidiurnal (L 2 ) tide in the Earth's atmosphere is unique as a purely mechanically forced periodic signal and it has been detected in upper atmosphere winds and temperature and in surface barometric pressure.L 2 signals in surface air temperature, L 2 (T), have only been detected at a single land station (results published almost a century ago). We report observational determinations ofL 2 (T) over the ocean by using data from 38 moored buoys across the tropical Pacific and Atlantic. In contrast to published speculation thatL 2 (T) should be negligible over ocean, we find that the observedL 2 (T) is fairly close to that consistent with an adiabaticL 2 pressure variation. Any deviations from purely adiabatic behavior are a measure of diabatic effects on the surface air—expected to be dominated by damping processes, notably heat exchange with the ocean surface. With the aid of climate model simulations that includeL 2 -tide-like variations, we demonstrate that our observations ofL 2 (T) provide a unique diagnosis for the strength of air-sea coupling and a useful constraint on climate model formulations of this coupling. Atmospheric Dynamics: Moon excites global surface air temperature wave Detection of air temperature variations forced by the lunar tide enables a novel diagnosis of the strength of air–sea coupling. The gravitational tidal force of the moon drives a roughly twice daily cycle in the atmosphere just as in the ocean. Earlier investigators had used long time series of barometric observations to quantify the surface air pressure variations associated with this lunar tide at many locations around the world. Takatoshi Sakazaki and Kevin Hamilton at the University of Hawai'i have now discovered comparable signals in the surface air temperature using two decades of observations at 38 moored buoys across the tropical Pacific and Atlantic. The relative amplitudes and phases of the lunar pressure and temperature signals are shown to provide valuable information about the exchange of heat between the atmosphere and underlying ocean surface.